The Student's Guide to Successful Project Teams - Kahn William A (Routledge - Taylor & Francis Group, 2009)
A core text on how to help student project teams confront and successfully resolve issues, tasks, and problems. Preface, Acknowledgements, Dimensions of the Student Project Team, The Learning Team, Team Formation, Team Roles and Responsibilities, Influence and Decision Making, Process Improvements, Useful Conflict, Full Engagement, Final Examinations, Project Team Exercises, References, Subject and Author Index.